The making of Tara Oceans: funding blue skies research for our Blue Planet - Eric Karsenti (Molecular Systems Biology)
Graphical Abstract Transforming a romantic idea into the large‐scale Tara Oceans project was made possible by risk‐taking funders that provided seed support to a self‐organized community of highly committed researchers.